The stratigraphy and metamorphism of the Snyder Group, Labrador - Speer, J. Alexander (Virginia Polytechnic Institute and State University, 1976)
The Snyder Group is a thin Aphebian sedimentary sequence unconformably overlying Archean rocks that has undergone deformation and a medium to high grade metamorphism as the result of the emplacement of the Elsonian Kiglapait intrusion. Five lithostratigraphic units totaling 239 m in thickness have been recognized: (1) a lower quartz arenite with local arkosic arenites, pelites, conglomerates, and a discontinuous basal conglomerate; (2) a manganiferous silicate iron formation; (3) a marble with associated calcsilicates and quartzites; (4) a sphalerite- and pyrrhotite-bearing quartz-rich, graphitic siltstone; and (5) an upper quartzite. Porphyritic andesite dikes and sills containing numerous subrounded basement xenoliths were emplaced before deformation and metamorphism. Later sills associated with the Elsonian Nain complex are also present. These intrusive rocks collectively have expanded the section to 355 m. The lower and upper quartzites with their high maturity, festoon and planar crossbedding, ripple marks, graded bedding, and numerous conglomerates were probably deposited in a shallow marine environment under tidal influence. The fine grain size, intraformational conglomerates, small-scale crossbeds, and thin bedding of the intermediate formations suggest that they were deposited in a quiet, shallow water environment disturbed only by occasional storms. The sedimentary features and thinness but great lateral extent of the lithologies suggest that the Snyder Group is an Aphebian platform assemblage. Three zones of metamorphic grade are defined by the aluminum silicates: I, andalusite; II, andalusite-sillimanite; III, sillimanite. Anatexis has occurred in zone III. The total width of the aureole is 2-2.5 km. Progressive metamorphic assemblages are: metapelites: Ia - and-chl-biot-musc-qz Mn gar ksp Ib - and-cord-biot-qz muse Mn gar ks II - and-sill-cord-biot-qz muse Mn gar + ksp III - sill-cord-biot-qz-ksp III - alm-cord-biot-qz-ksp III - opx-alm-cord-biot-qz-ksp metabasites: I - chl-epid-green hbl-biot-pc-qz ...